2019
DOI: 10.5902/1980509834590
|View full text |Cite
|
Sign up to set email alerts
|

Características físico-hídricas de substratos formulados com lodo de esgoto na produção de mudas de acácia-negra

Abstract: Avaliou-se o efeito da retenção de água de substratos para plantas formulados a partir de diferentes proporções de lodo de esgoto (LETE) solarizado, na produção de mudas de acácia-negra (Acacia mearnsii). O experimento foi conduzido em casa de vegetação e no Laboratório de Física do Solo da Embrapa Clima Temperado. O LETE utilizado foi coletado em leitos de secagem de uma Estação de Tratamento de Esgoto aeróbio de Rio Grande - RS. Os tratamentos consistiram de cinco doses de LETE solarizado, combinadas com cin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…In contrast to the results obtained in the present study, Siqueira et al (2019), when evaluating the use of treated sewage sludge in the substrate composition of Plathymenia reticulata seedlings, found that the lowest proportion of sewage sludge (20%) in then two mixtures tested was the most suitable for the evaluated crop, with growth patterns similar to those produced with commercial substrates. Similar results were found by Monteiro et al (2019), who evaluated the effect of increasing proportions of SASS on the water retention of substrates and the agronomic performance of black wattle (Acacia mearnsii) seedlings. The substrate with 20% SASS, 40% vermiculite, and 40% rice husk ash presented the best physical-hydraulic conditions for the development of black wattle seedlings in the period from germination to transplantation.…”
Section: Agronomic Performancesupporting
confidence: 82%
See 2 more Smart Citations
“…In contrast to the results obtained in the present study, Siqueira et al (2019), when evaluating the use of treated sewage sludge in the substrate composition of Plathymenia reticulata seedlings, found that the lowest proportion of sewage sludge (20%) in then two mixtures tested was the most suitable for the evaluated crop, with growth patterns similar to those produced with commercial substrates. Similar results were found by Monteiro et al (2019), who evaluated the effect of increasing proportions of SASS on the water retention of substrates and the agronomic performance of black wattle (Acacia mearnsii) seedlings. The substrate with 20% SASS, 40% vermiculite, and 40% rice husk ash presented the best physical-hydraulic conditions for the development of black wattle seedlings in the period from germination to transplantation.…”
Section: Agronomic Performancesupporting
confidence: 82%
“…This result is related to the greater capacity of SASS to supply N, P, Ca, Mg, S, and micronutrients (Table 1), while the physical-hydraulic characteristics were maintained at the optimal interval. Monteiro et al (2019) and Monteiro et al (2021), when evaluating the chemical characteristics of substrates with different doses of sewage sludge and carbonized rice husks, found that the amount of nutrients increased with an increase in the percentage of sewage sludge in the substrate. Many studies addressing the use of sewage sludge in agriculture state that it is a source of nutrients in substrates, particularly P, N, and Ca (Guerrini & Trigueiro, 2004;Santos et al, 2014;Monteiro et al, 2020b).…”
Section: Agronomic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…In the seedling production phase, the substrate is one of the most important elements, directly influencing germination and the development of the root system of the new plants, besides being responsible for providing nutrients and retaining water throughout the seedling formation process (Barreto and Testezlaf, 2014;Alves et al, 2021). In the elaboration of a substrate, rarely will only one material count with all the attributes suitable for the particular plant species (Rodrigues et al, 2016), being necessary to mix different raw materials, becoming a challenge since the final quality of the substrate will be the result of the characteristics and interactions of the materials used (Monteiro et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to researchers, several practices have been developed to increase the quality and reduce the costs of seedling production, such as the use of renewable materials (TRAZZI et al, 2013;MARQUES et al, 2018a;MONTEIRO et al, 2019). These materials are sources of nutrients, being an alternative for the disposal of waste, reducing the possible socio-environmental problems they cause when incorrectly discarded (SANTOS et al, 2017).…”
Section: Introductionmentioning
confidence: 99%